A contribution to the gross anatomy of human extra-hepatic bile ducts with multi slice computed tomography - Castorina, Sergio; Luca, Tonia; Privitera, Giovanna; Riccioli, Vincenzo; Musumeci, Giuseppe; Loreto, Carla (Italian Journal of Anatomy and Embryology, 2017)
Considering the high risk of biliary lesions during laparoscopic cholecystectomy the anatomy of the biliary tree has been the object of increasing interest. The aim of this study is mapping the extra hepatic biliary topography by 64-Multislice Computed Tomography, in patients who had undergone surgery for choledocolithiasis using T - Tube inside common bile duct.. This technique allows to remove virtually the liver parenchyma, and with the subsequent three-dimensional reconstruction of images, represents a good tool to visualise the biliary ducts. With 3 D reconstruction we are able to create the topography of extra hepatic ducts visible in several projections. We have selected 15 cases. Principal variants regard the morphology of cystic duct. This technique allows to map the biliary tract alternativamente to classic anatomical dissection, realizing a source of data directly from surgery. Furthermore it is possible to use the data in case of biliary iatrogenic lesion with legal sequences.